(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
Soil degradation, including salinization and erosion, is a significant environmental issue in Uzbekistan, severely affecting agricultural productivity and food security. This study explores the causes, processes, and consequences of soil degradation in the country, with a focus on the role of improper irrigation practices and unsustainable farming techniques. The research highlights the correlation between soil degradation and reduced crop yields, with salinity alone leading to a decrease in agricultural production by up to 70%. The study also examines the response of the Uzbek government, including the implementation of policies like Presidential Decree PQ-71, aimed at sustainable land management and soil fertility restoration. Furthermore, the research emphasizes the potential of eco-friendly solutions, such as microbial applications, to mitigate soil salinity and improve soil health. The findings of this study provide valuable insights for policymakers and farmers, offering innovative strategies to combat soil degradation and ensure long-term agricultural sustainability in Uzbekistan